2022
DOI: 10.1186/s12889-022-12757-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between social media use and the acceptance of COVID-19 vaccination among the general population in Saudi Arabia – a cross-sectional study

Abstract: Background The Coronavirus Disease of 2019 (COVID-19) pandemic is a worldwide global public health threat. Although acceptance of COVID-19 vaccination will be a critical step in combating the pandemic, achieving high uptake will be difficult, and potentially made more difficult by social media misinformation. This study aimed to examine the association between social media use and acceptance of receiving COVID-19 vaccine among the general population in Saudi Arabia. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The results align with previous studies linking gender to a greater probability of experiencing post-vaccination side effects and more severe symptoms but differed from prior research indicating that gender has no impact on the side effects. 18 , 20 - 23 Although there is yet no consensus on the influence of gender on the onset and specific symptoms experienced after COVID-19 vaccination, the results of this study support the need to explain to the female population on the higher possibility of experiencing symptoms that may require or not require hospitalization. All age groups report common symptoms, but the participants who reported no symptoms and who reported mild, moderate, and severe symptoms were comparatively younger ( Table 3 ).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The results align with previous studies linking gender to a greater probability of experiencing post-vaccination side effects and more severe symptoms but differed from prior research indicating that gender has no impact on the side effects. 18 , 20 - 23 Although there is yet no consensus on the influence of gender on the onset and specific symptoms experienced after COVID-19 vaccination, the results of this study support the need to explain to the female population on the higher possibility of experiencing symptoms that may require or not require hospitalization. All age groups report common symptoms, but the participants who reported no symptoms and who reported mild, moderate, and severe symptoms were comparatively younger ( Table 3 ).…”
Section: Discussionsupporting
confidence: 48%
“…The results were partly similar to a previous study indicating that young people have a higher proportion of side effects and partly aligned with studies showing that age has no statistically significant impact on vaccine symptoms. 18 , 20 - 23 More participants belonged to the younger age groups so more of those who reported no side effects were younger people and more of those who reported side effects of various severity were also younger people. Age does not seem to be a conclusive determinant of the onset of side effects or the occurrence of specific side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the COVID-19 vaccine hesitancy rate in Saudi Arabia varied significantly between studies, ranging from 5% to 82%. The lowest hesitancy rates (<10%) were reported by 2 studies, 26 , 45 whereas higher rates (>30%) were reported in 22 studies. 14–17 19–24 27–33 35–37 39–44 Several factors were found to be associated with vaccine hesitancy, including concerns about vaccine safety (n = 18), 16–20 22–26 29–31 36–38 40–42 45 concerns about vaccine effectiveness (n = 16), 16 17-19 22-24 30-33 36-38 40-42 45 belief that the vaccine has not been tested sufficiently (n = 7), 20–24 26–30 , 31–45 belief in conspiracy theories (n = 4), 22 , 29 , 39 , 40 belief in natural immunity following COVID-19 infection (n = 2), 30 , 39 a history of chronic illnesses (n = 2), 31 , 45 a fear of injections (n = 2), 30 , 44 and mistrust in pharmaceutical companies (n = 1).…”
Section: Resultsmentioning
confidence: 83%
“…For this study, vaccine acceptance was re-categorized as willingness (4−5) and unwillingness (1−3). Participants who were unwilling to be vaccinated were additionally asked to indicate the main reasons for their unwillingness [27] .…”
Section: Methodsmentioning
confidence: 99%